The Effect of Puzzle as Health Education Media on Knowledge and Attitude of DHF Prevention Among Trash Warrior Community - Aris Mudariani; Ni Komang Ari Sawitri; Indah Mei Rahajeng; Putu Ayu Sani Utami (Talenta Publisher, 2023)
Dengue Haemorrhagic Fever (DHF) is a significant public health threat that can be controlled by engaging all community groups in preventive measures. Interventions targeting early age are pivotal in improving knowledge and attitudes toward DHF prevention. This study proposes a health promotion strategy using a Puzzle as an educational media targeting the Trash Warrior Community members aged 9-12 years to enhance knowledge and attitudes towards DHF prevention. This was a pre-experimental study with a one-group pretest-posttest conducted from February to March 2023. All Trash Warrior Community members aged 9 – 12 (n=20) were included as respondents. They were given a questionnaire consisting of 13 questions of knowledge and ten statements of attitudes towards DHF prevention before and after the health education. The intervention in this study was health education using puzzles in 5 small groups, each consisting of 4 children. Each group was given 30 minutes to arrange the puzzle. This study shows an improvement of mean value on knowledge for 2.1 points and attitude for 0,75 points. Based on the result of bivariate analysis using the Wilcoxon test, it was found that there was a significant effect of education using puzzle media on knowledge (p=0.000, p<0.05) and attitudes (p=0.045, p<0.05) in preventing DHF among Trash Warrior Community members aged 9-12 years. Health education using puzzles effectively increases children’s knowledge and attitude toward DHF prevention.